First record of non-native hybrid catfish Pseudoplatystoma reticulatumxLeiarius marmoratus in the Upper Parana River basin, Brazil - Yabu, M. H. S.; Vidotto-Magnoni, A. P.; Casimiro, A. C. R.; Garcia, D. A. Z.; Costa, A. D. A.; Prado, F. D. D. [UNESP]; Porto-Foresti, F. [UNESP]; Orsi, M. L. (Wiley-Blackwell, 2018)
The aim of this study is to report the presence of a three non-native hybrid long-whiskered catfishes (family Pimelodidae) in the Upper Parana River basin, Brazil. Genetic analyses demonstrated that the three presumptive hybrids were a result of the crossbreeding of Pseudoplatystoma reticulatum (central Amazonas River basin and Lower Parana River) and Leiarius marmoratus (Amazonas, Essequibo and Orinoco rivers), producing a hybrid commonly known in Brazil as cachandia. The potential threat to biodiversity, due to possible genetic contamination, competition and predation of wild stocks, of such artificially produced hybrid fishes is discussed.
Keywords: conservation; hybridization; long-whiskered catfishes; non-native fish; South America